2022
DOI: 10.3389/fenvs.2022.1085326
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of porous materials by the modification of coal fly ash and its environmentally friendly use for the removal of heavy metals from wastewater

Abstract: Wastewater is a complex mixture of many pollutants, where the high-risk pollutants are heavy metals (HMs) in industrial wastewater due to their difficult removal. In this study, the waste CFA was used as the main raw material for production of new innovated flocculants porous particles by modification of coal fly ash (CFA) using a multi-step base–acid–base (NaOH–HCl–NaOH) modification method. The morphological structure and elemental composition of the prepared MCFA were analyzed through characterization analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…1 ), microwave irradiation, ultrasound and fusion techniques. When compared to untreated CFA, modified-CFA demonstrated considerably higher levels of trace metal adsorption capacity [ 51 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ), microwave irradiation, ultrasound and fusion techniques. When compared to untreated CFA, modified-CFA demonstrated considerably higher levels of trace metal adsorption capacity [ 51 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…When CFA was impregnated with Fe and Al, the adsorption of Ni (II), Zn (II) and Cr (VI) was highly improved [ 66 ]. Using enthalpy change data, it was determined that adsorption was exothermic for Ni (II) and endothermic for Zn (II) [ 51 , 65 ]. Hussain et al [ 51 ] found that the alkaline character of the CFA neutralizes the metal solution, which is linked to the removal efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation